Social support and physical activity in over the road truck drivers - McGough, Leigh A. (My University, 2011)
With sedentary lifestyles at the heart of the obesity epidemic, finding ways to increase physical activity is imperative. Certain populations may encounter unique barriers to increasing physical activity, such as over the road truck drivers (OTRTD). In 2006, a U.S. Department of Transportation survey showed that 90% of truck drivers were overweight and 50% were obese, leading to an increased prevalence in chronic health conditions. Current research indicates a limited number of studies that have focused on decreasing weight and increasing physical activity in OTRTDs. The purpose of this study was to determine if there was a relationship between social support and the level of physical activity in over the road truck drivers. Pender's Health Promotion Model(HPM) was used as the theoretical framework for this study. The HPM identifies individual characteristics and experiences that affect subsequent health actions, such as exercise and social support. Concepts such as interpersonal influences, situational influences, and support with committing to a plan of action all use social support to increase health outcomes. Over the road truck drivers can benefit from using health-promoting behaviors due to the nature of their work environment. A quantitative descriptive correlational research design was used for this study. A convenience sample of 42 participants was obtained from two different truck stop locations in the Midwest. A demographic Truck Driver Questionnaire, the Norbeck Social Support Questionnaire (NSSQ), and the International Physical Activity Questionnaire (IPAQ) were administered. Data were analyzed using descriptive and inferential statistics. Results indicated that there was no significant correlation between total social support and total physical activity scores (p=.840). No significant correlations were demonstrated between the NSSQ emotional support subscale and the IPAQ total physical activity score (p= .652) or the NSSQ tangible support of the NSSQ and the IPAQ total physical activity score (p= .696.) Although the results of the study were not statistically significant, there are important implications for practice and research. Providers need to address the unique barriers encountered by OTRTDs and discuss more creative and helpful ways to increase levels of physical activity. Future studies should look at more appropriate tools for this population and take into account the environment in which the study takes place. A qualitative study could provide more insight into the perceptions of exercise and healthy eating, and the specific challenges facing OTRTDs.
A Clinical Paper submitted in partial fulfillment of the requirements for the degree of Master of Science in Nursing-Family Nurse Practitioner
Keywords: Truck drivers - Nutrition; Truck drivers - Family relationships; Truck drivers - Health and hygiene